The formation of striated structures in dust tails of comets - S. V. Kharchuk; P. P. Korsun (Вісник Астрономічної школи, 2012)
The mechanism of formation of striae structures in the dust tails of comets is proposed. There are local active areas on the surfaces of comet nucleus. The formation of striae is indebted to the different rate of dust ejection from active areas depending on that they are located on the sunlit or shaded side of the rotating nucleus. The model analysis of dust tails forming of comets C/1957 P1 (Mrkos), C/1962 C1 (Seki-lines), C/1910 A1 (Great January Comet), C/1975 V1 (West) showed that the proposed mechanism can explain the formation of striae.